Acute Urinary Morbidity Following Stereotactic Body Radiation Therapy for Prostate Cancer with Prophylactic Alpha-Adrenergic Antagonist and Urethral Dose Reduction - Repka, Michael C.; Guleria, Shan; Cyr, Robyn A.; Yung, Thomas M.; Koneru, Harsha; Chen, Leonard N.; Lei, Siyuan; Collins, Brian T.; Krishnan, Pranay; Suy, Simeng; Dritschilo, Anatoly; Lynch, John; et al. (Frontiers in Oncology, 2016)
Background: Stereotactic body radiation therapy (SBRT) delivers high doses of radiation to the prostate while minimizing radiation to adjacent critical organs. Large fraction sizes may increase urinary morbidity due to unavoidable treatment of the prostatic urethra. This study reports rates of acute urinary morbidity following SBRT for localized prostate cancer with prophylactic alpha-adrenergic antagonist utilization and urethral dose reduction (UDR). Methods: From April 2013 to September 2014, 102 patients with clinically localized prostate cancer were treated with robotic SBRT to a total dose of 35-36.25 Gy in 5 fractions. UDR was employed to limit the maximum point dose of the prostatic urethra to 40 Gy. Prophylactic alpha-adrenergic antagonists were initiated five days prior to SBRT and continued until resolution of urinary symptoms. Quality of life (QoL) was assessed before and after treatment using the American Urological Association Symptom Score (AUA) and the Expanded Prostate Cancer Index Composite-26 (EPIC-26). Clinical significance was assessed using a minimally important difference (MID) of one half standard deviation change from baseline. Results: 102 patients underwent definitive prostate SBRT with UDR and were followed for 3 months. No patient experienced acute urinary retention requiring catheterization. A mean baseline AUA symptom score of 9.06 significantly increased to 11.83 one-week post-SBRT (p = 0.0024) and 11.84 one-month post-SBRT (p = 0.0023) but returned to baseline by 3 months. A mean baseline EPIC-26 irritative/obstructive score of 87.7 decreased to 74.1 one-week post-SBRT (p < 0.0001) and 77.8 one-month post-SBRT (p < 0.0001) but returned to baseline at 3 months. EPIC-26 irritative/obstructive score changes were clinically significant, exceeding the MID of 6.0. At baseline, 8.9% of men described their urinary function as a moderate to big problem, and that proportion increased to 37.6% one week following completion of SBRT before returning to baseline by three months. Conclusions: SBRT for localized prostate cancer with utilization of prophylactic alpha-adrenergic antagonist and UDR was well tolerated as determined by acute urinary function and bother, and symptoms were comparable to those observed following conventionally fractionated external beam radiation therapy (EBRT). Longer follow-up is required to assess long-term toxicity and efficacy following SBRT with UDR.